Teacher and Student Responses to Educational Games Based on the Fisher-Yates Shuffle Algorithm in Learning Advertising Texts, Slogans, and Posters - Putri, Ermira Nilansari; Rahmawati, Laili Etika; Sufanti, Main; Mansoor, Hafiza Sana (Universitas Muhammadiyah Malang, 2024)
The suitability of games as an effective learning medium provides deep insight into the interactions between teachers and students in innovative learning contexts. The purpose of this research is to (1) describe students' active responses to the “TISTER” application as an Android-based learning media and (2) describe teachers' responses to the “TISTER” application as an Android-based learning media. Qualitative descriptive method with a case study model. The research subjects in this study were VIIIC students and Indonesian language teachers at SMP Negeri 2 Jatisrono. The research object includes student and teacher responses to educational games. Research data is information and facts. Primary data sources are direct observations, interviews, and questionnaire instruments. Data was collected through in-depth interviews with teachers, classroom observations when the application was used, and questionnaire analysis of class VIIIC student responses. Testing the validity of this data was carried out using source triangulation techniques. Data analysis method by Miles and Huberman. The results of research on student responses showed that there was an increase in activity of 87%, while 13% felt that they had not experienced an increase in activity. The results of the research on teacher responses were the suitability of the aspects assessed (material content, learning objectives, targets, completeness, and relevance of the content). The percentage of assessments from teacher 1's responses to indicators 1-5 (V1-V5), namely 80%, 82%, 80%, 86% and 82%. Teacher responses in terms of material and media aspects in educational games were reviewed by two teachers each against five performance indicators (V1-V5).